Moisture Use Pattern and Yield of Hybrid Sorghum under Different Moisture Conservation Practices on Vertic Ustochrept - Kalane, R.L.; Sagare, B.N.; Guhe, Y.S.; Marathe, R.A. (Journal of Soil and Water Conservation, 2022)
A field experiment was conducted on Vertic Ustochrept during Kharif 1988 for investigating moisture use pattern and production potential of hybrid sorghum under different moisture consmatiort practices. Highest grain yield of 10-. Sorghum (2530.4 Kg ha-5 was obtained under vertical mulch and it was at par under broad base furrow. Per cent increase in grain yield over that of the crop SOltil across the slope was found as 12.42, 27.68 and 34.27, respectively due to contour sowing, broad base fuorrow and vertical mulch treatments.